Modular development in Java - Shamanin, Kirill; Pecinovský, Rudolf, 1954-; Oraný, Vladimír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
On September 21st, 2017 Oracle released new version of Java language, Java 9. Java 9 was under development for 3 years, which is a long time for an update of a programing language. The new version includes a vast list of changes and new features; among them is support for HTML 2.0 or JShell (tool for a command line) and project Jigsaw. Jigsaw was long time in development; the goal of the project was to bring modularity to Java language. This work is mainly focused on research of modularity impact on Java programing lan-guage. The crucial difference between old and new programing concept in Java is ana-lyzed. Particular changes for developers are discussed.
Vedoucí práce: Rudolf Pecinovský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses